The Influences of Professional Competence and Teacher Commitment on Learning Quality at Hikmah Sejati Foundation in Banda Aceh - Lubis, Nuraini; Murniati, Murniati; Usman, Nasir (FKIP Universitas Lampung, 2021)
The purpose of this study is to find out whether there are the influences of professional competence and teacher commitment to the learning quality. This research uses the quantitative approach with descriptive method. The population of this research was all teachers at Hikmah Sejati Foundation Banda Aceh. The sample used in this research was 100 people. Moreover, the data analysis used in this research was multiple linear regression. This result shows that: (1) partially, the professional competency variable is in good correlation with the percentage of 53 on the learning quality (2) partially, the teacher commitment variable has a fair correlation with the percentage of 33 on the learning quality (3) simultaneously the professional competence and teacher commitment variables have a good correlation with the percentages of 58% on learning quality. The research result obtained based on the multiple linear regression equation was Y = 25,655 + 0,631X1 + 0,43X2 of correlation coefficient is 0.762. According to statistic test Fscore= 67,021 >Ftable = 3.09 , with probability level of 0.000. Therefore, there is a significant correlation between professional competence and teacher commitment to learning quality. Keywords: profesional competence, teacher commitment, learning quality. DOI: 10.23960/jpp.v11.i2.202122